DIGITALISASI PERKEMBANGAN WAKAF DI KALANGAN KAUM MILENIAL - Ratna; Darsi Ahmadan; Hairun Nisa; Hidayani; Itsnaini Chusnul Khotimah (ADL ISLAMIC ECONOMIC : Jurnal Kajian Ekonomi Islam, 2023)
This study aims to examine and analyze the development of waqf through digitalization of waqf automatically opening wider opportunities and better prospects in various fields. It is time for the millennial generation to take a more active role in the development and progress of waqf in Indonesia. It can be said that the millennial generation is the most important key for the development of waqf and the improvement of the Indonesian economy globally. Millennials have special qualities that set them apart from other circles. Millennials are very familiar with the use of communication tools, media and digital technology. His interest in reading is reduced because of his fondness for gadgets as a means of reading. His knowledge of digital media also exceeds his knowledge of books. All these tools because they were born at a time when communication device technology was developing rapidly. In today's digital economy era, computers (PCs) and the Internet are the main technologies used for various daily needs. Waqf funds or assets can be empowered to help provide good sanitation facilities in the community and provide clean water sources. If possible waqf funds can also help the weak live in an alarming stage Keywords: Waqf, Digitalisasi, Digitalisasi of Waqh